The Effect of Hedging Strategies on the Financial Performance of Import-Export Companies in Indonesia - Eva Purnamasari; Arisha Putri Pradita; Mega Arum; Junet Kaswoto; Abdul Karim (West Science Interdisciplinary Studies, 2025)
This study examines the effect of hedging strategies on the financial performance of import–export companies in Indonesia. Due to the high exposure to foreign exchange fluctuations, firms engaged in international trade increasingly adopt hedging mechanisms to stabilize financial outcomes. Using a quantitative approach, data were collected from 115 respondents through a Likert scale–based questionnaire and analyzed using SPSS version 25. Statistical tests including validity, reliability, correlation, and regression analyses were conducted to evaluate the relationship between hedging strategies and financial performance. The results show that hedging strategies have a positive and significant effect on financial performance. The correlation coefficient (r = 0.642) indicates a strong relationship, while the regression analysis reveals that hedging explains 41.2% of the variation in financial performance. Forward contracts, options, swaps, and natural hedging contribute significantly to improving profitability, liquidity, and cash flow stability. The findings highlight the importance of systematic risk management practices in increasing the financial resilience and competitiveness of import–export companies in Indonesia. This study recommends that firms enhance their financial literacy and adopt more structured hedging policies to effectively mitigate currency risks.